2021
DOI: 10.26717/bjstr.2021.33.005391
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Nutrition Education on Nutritional Status of Tuberculosis Patients

Abstract: Tuberculosis (TB) is a major global health problem and is related to poverty, under nutrition and poor immune function. The nutrition education provides guidance on the nutritional care and support for patients with tuberculosis. Current study was aimed to investigate the effect of nutrition education on nutritional status of tuberculosis patients. This was a pre and post interventional study conducted at Gulab Devi Chest hospital Lahore during December 2016 to February, 2017 among 100 patients of pulmonary tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Effective nutrition-specific and nutrition-sensitive interventions have been implemented to improve the nutritional status of vulnerable groups particularly children and women [15]. Though evidence about the potential interventions to improve the nutritional status of TB patients is limited, a pre-post intervention study reported that nutrition education can improve the nutritional status of TB patients [16]. More importantly, given the complex relationship between nutrition and infections [17], nutrition assessment, counseling, and support (NACS) is suggested for patients with HIV and/or TB.…”
Section: Introductionmentioning
confidence: 99%
“…Effective nutrition-specific and nutrition-sensitive interventions have been implemented to improve the nutritional status of vulnerable groups particularly children and women [15]. Though evidence about the potential interventions to improve the nutritional status of TB patients is limited, a pre-post intervention study reported that nutrition education can improve the nutritional status of TB patients [16]. More importantly, given the complex relationship between nutrition and infections [17], nutrition assessment, counseling, and support (NACS) is suggested for patients with HIV and/or TB.…”
Section: Introductionmentioning
confidence: 99%